2003
DOI: 10.1093/jnci/95.3.214
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 Germline Mutations in Familial Pancreatic Carcinoma

Abstract: Our data support an important role for BRCA2 germline mutations in a subpopulation of families with familial pancreatic cancer. BRCA2 mutation analysis should be included in molecular genetic testing and counseling strategies in families with at least two first-degree relatives affected with ductal adenocarcinoma of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
226
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(233 citation statements)
references
References 28 publications
3
226
0
4
Order By: Relevance
“…It has been reported that BRCA2, PALB2, and ataxia telangiectasia mutated germ‐line mutations are most frequently identified in familial PC cases 32, 33, 34. In July 2013 in Japan, JPS established the familial PC registry for early diagnosis, and already started this registry in 2015.…”
Section: Risk Factors and Early Diagnosismentioning
confidence: 99%
“…It has been reported that BRCA2, PALB2, and ataxia telangiectasia mutated germ‐line mutations are most frequently identified in familial PC cases 32, 33, 34. In July 2013 in Japan, JPS established the familial PC registry for early diagnosis, and already started this registry in 2015.…”
Section: Risk Factors and Early Diagnosismentioning
confidence: 99%
“…Familial pancreatic cancer is defined as cancers occurring in families in which there are at least two firstdegree relatives with the disease in the absence of other known familial cancer syndromes. The inherited basis of B10-20% of familial pancreatic cancers has been identified and is reflected largely in germline mutations in the BRCA2 gene (Goggins et al, 1996;Ozcelik et al, 1997;Hahn et al, 2003) (The Breast Cancer Linkage Consortium, 1999;Murphy et al, 2002). Germline mutations in the p16 (Goldstein et al, 1995;Lynch et al, 2000;Vasen et al, 2000;Bartsch et al, 2002), FANCC (van der Heijden et al, 2003;Rogers et al, 2004), FANCG (van der Heijden et al, 2003;Rogers et al, 2004), PRSS1 (Lowenfels et al, 1993(Lowenfels et al, , 1997, STK11 (Giardiello et al, 2000;Lim et al, 2004), and hMLH1 (Yamamoto et al, 2001) genes are infrequent causes of familial pancreatic cancer and are associated with a number of cancer syndromes, including familial multiple mole melanoma (FAMMM), hereditary pancreatitis, hereditary nonpolyposis colon cancer, and Peutz-Jeghers syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, germline BRCA2 mutations are observed in B5% of patients with apparently sporadic pancreatic cancer, that is, patients who do not appear to have an inherited predisposition to pancreatic or breast/ovarian cancer (Goggins et al, 1996;Ozcelik et al, 1997;The Breast Cancer Linkage Consortium, 1999;Figer et al, 2001). Murphy et al (2002) recently reported deleterious BRCA2 mutations in up to 17% of familial pancreatic cancers and Hahn et al (2003) found a prevalence of B12%.…”
Section: Introductionmentioning
confidence: 99%
“…Germline BRCA2 mutations are identified in 4-17% of families with familial PDAC and are the most common germline genetic alteration identified in this condition (Murphy et al 2002, Hahn et al 2003, Couch et al 2007, Salo-Mullen et al 2015, Zhen et al 2015, Hu et al 2016, Roberts et al 2016. However, this rate varies depending on the definition of familial PDAC, i.e., the number of relatives affected to define a population at risk.…”
Section: Epidemiological Links Between Brca2 Mutations and Pdacmentioning
confidence: 99%